Characterization of the H+/peptide cotransporter of eel intestinal brush-border membranes. - VERRI, Tiziano; MAFFIA, Michele; DANIELI, Antonio; STORELLI, Carlo; M. HERGET; U. WENZEL; H. DANIEL (2000)
H+/peptide cotransport in brush-border membrane vesicles (BBMVs) from eel (Anguilla anguilla) intestine was studied by measuring D-[H-3]-phenylalanyl-L-alanine uptake and by monitoring peptide-dependent intravesicular acidification using the pH-sensitive dye Acridine Orange, D-[H-3]-phenylalanyl-L-alanine influx was greatly stimulated by an inside-negative membrane potential and enhanced by an inwardly directed H+ gradient. In parallel, vesicular Hf influx was significantly increased in the presence of extravesicular D-phenylalanyl-L-alanine or a series of glycyl and L-prolyl peptides. H+/peptide cotransport displayed saturable kinetics involving a single carrier system with apparent substrate affinities of 0.9-2.6 mmol l(-1) depending on the particular peptide. All substrates tested competed with this system. Pre-incubation of BBMVs,vith dipeptides prevented diethylpyrocarbonate inhibition of transport activity, suggesting that the substrates mask histidine residues involved in the catalytic function of the transporter. Using human PepT1-specific primers, a reverse transcriptisn-polymerase chain reaction (RT-PCR) signal was detected in eel intestine. Our results suggest that, in eel intestine, a brush-border membrane 'low-affinity'-type H+/peptide cotransport system is present that shares kinetic features with the mammalian intestinal PepT1-type transporters.